Analysis of rectifier circuits for low power and sensing applications - Khan, Imran Moez; Khan, Sheroz; Khalifa, Othman Omran; Alam, A. H. M. Zahirul (2011)
Transducers are used for many different applications in industry such as liquid-level sensing, pH monitoring, or gas pressure recording. However, sometimes these sensors need to be located in areas where wiring is not possible, such as in application of implanted biomedical devices. Some challenges that that must be overcome include the wireless power supply of sensors, accurate and steady DC reference, load-matching of circuitry, linearity of the measurements and the modulation of data. This paper investigates two types of rectification for power transfer in implanted sensor applications and the use of rectifier for phase and level modulation via Load-Shift Keying (LSK).